Physical therapy evaluation in the immediate post-operative period of patients with lower limbs amputation assisted at the hospital bedside/ Avaliação fisioterapêutica no pós-operatório imediato do paciente amputado de membros inferiores atendido à beira do leito hospitalar - Sarmento, Tuane; Luz, Soraia Cristina Tonon da; Oliveira, Elaine Ferreira de (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Lower limb (LL) amputation compromises the individual’s quality of life and functionality, requiring immediate rehabilitation through the assistance of a multiprofessional team. This research describes the sociodemographic and physicalfunctional profile of the LL amputee, evaluated at the hospital bedside in the immediate postoperative period. This is a descriptive and cross-sectional study in which patients from the Unified Health System were evaluated, who underwent LL of any etiology in a public hospital. The collection was designated through notifications from the hospital staff regarding cases of newly amputees, totaling fourteen subjects. The average age of the participants was 44 years old, being 86% male. The etiology of the predominant amputation was automobile trauma due to motorcycle accidents and transtibial level. From the perimetry, it was found that 43% of the individuals presented edema in the stump when compared to the contralateral limb. Regarding stump pain, 93% of subjects reported feeling, while 78% reported feeling phantom pain and phantom sensation. Concerning normal muscle strength in the amputated limb, it was present in only 1% of patients, in contrast to the intact limb was present in 48% of individuals for any muscle group. In bed mobility, 32% of individuals had complete independence. In unipodal orthostatism, no patient was able to stand independently. From the collected data it was possible to conclude that the physical therapist should pay attention to the muscular strength, bed mobility, and static balance of the amputee to avoid muscle contractures and facilitate prosthesis.